Hubungan Antara Motivasi dan Keikutsertaan dalam Ekstrakurikuler Olahraga Beregu di SMP 9 Cimahi - Fahreza Maulana Nugraha; Kurnia Eka Wijayanti; Yusuf Hidayat (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
The research of this study is to examine the relationship between motivation and participation in team sports extracurricular activities among students in year 7 and 8 at SMP Negeri 9 Cimahi. This study argues that even though there are various benefits from participating in team sports extracurricular activities, students' involvement vary. Some students participating actively and consistently while others attend irregularly. This study employed a quantitative approach with a correlational design. The population in this study were 250 students at SMPN 9 Cimahi who participated in team-based extracurricular activities, and 148 were active students and were used as the research sample through total sampling. Data were collected using a questionnaire based on a 1–4 Likert scale. The instrument was adapted from the Sport Motivation Scale-II (SMS-II) to measure students' motivation, and the Participation Motivation Questionnaire (PMQ) to measure students' participation. Descriptive analysis shows that average students' motivation was categorized as moderate (mean = 50.36, SD = 5.091), with relatively homogeneous scores among respondents. Correlation test showed a correlation coefficient of rs = 0.376 with a significance value of 0.000 (p < 0.01), indicating a significant positive relationship between motivation and participation. These findings suggest that motivation is a meaningful contributing factor to students' participation in team sports extracurricular activities. Keywords: Team Sports Extracurricular, Participation, Motivation